Currículo de formação inicial de professores de um curso de Licenciatura em Letras a distância - Sensato, Marisa Garbellini (2022)
Distance teacher training is a reality in Brazilian higher education, a field that grows fast and enables higher education access expansion in the country. This research was developed in this context, having as main goal to critically analyze the curriculum and the technology integration of a distance learning degree in Portuguese offered by Universidade Aberta do Brasil (UAB), carried out from 2014 to 2018. To this end, it was carried out a case study in order to: analyze the curriculum design that guides the pedagogical project of the course in focus; identify the specificities of the curriculum of the course prescribed and developed in the training in focus; analyze the integration between this curriculum and digital information and communication technologies as well as understand the presence of web curriculum indicators; and recognize how the curriculum is materialized in the practices carried out in the course. For the development of this netnographic case study, it was adopted a qualitative approach based on a bibliographic study and a documental analysis, in addition to a semistructured interview with professors and course graduates. The context consists of a public and free distance degree in Portuguese, held in a center of Rede Universidade nos Centros Educacionais Unificados (UniCEU) in the city of São Paulo. The research subjects were six graduates and two professors of the course. The empirical material collected was analyzed in accordance with the theoretical frameworks of curriculum, teacher training and Digital Information and Communication Technologies (DICT) in Education. The analysis showed that the prescribed curriculum of the course advocates the integration of DICT in teacher training regarding the subjects’ critical use of DICT in pedagogical practices.The analysis of these practices indicated that changes and innovations are strongly connected with teacher training in the course. The participating teachers stated that they re-signified their practices based on their performance in this distance course. As for the curricular innovations, the research findings reveal that this process is hampered by the discontinuity of public policies for teacher training; by the excess of curricular guidelines defined by the Ministry of Education (MEC); by the lack of investments in education in Brazil; and for noncompliance with the National Education Plan (PNE). The data showed the need for national debates on the curriculum guidelines for degrees in Languages and on the Curriculum National Base for Teacher Training. The need for theoretical and in-depth studies was also identified by the professionals who design curricular policies and curricula for teacher training, giving special attention to the comprehension of the concept of curriculum and its design in distance courses and the integration of these courses into the context of higher education as well as the strengthening of the teachers’ role to build pedagogical practices